A Simple Approach towards High‐Performance Perovskite‐Based Bifunctional Oxygen Electrocatalysts. Issue 1 (28th October 2015) - Elumeeva, Karina; Masa, Justus; Tietz, Frank; Yang, Fengkai; Xia, Wei; Muhler, Martin; Schuhmann, Wolfgang
Abstract: To accelerate the large‐scale commercialization of electrochemical energy storage and conversion technologies through water splitting and regeneration in reversible fuel cells, cost‐effective, highly efficient, and durable reversible oxygen electrodes are required. We report a comparatively simple approach to modify a group of oxygen‐evolving perovskites based on lanthanum cobaltite into effective bifunctional systems through partial atom substitution, which, upon intermixing with nitrogen‐doped carbon nanotubes, achieve remarkably low round‐trip overvoltage of <850 mV in the electrocatalysis of oxygen reduction and oxygen evolution in an alkaline electrolyte, KOH (0.1 m ). Besides the bifunctional electrocatalytic performance, the composite systems with a low Fe content possessed promising long‐term stability. Abstract : Left to their own devices : A simple procedure is introduced to design bifunctional electrocatalysts for the oxygen evolution and oxygen reduction reactions (OER/ORR) in alkaline electrolytes. The low overpotential difference achieved between oxygen evolution and oxygen reduction for the bifunctional catalysts demonstrates that perovskite/N‐doped carbon nanotube composites have the potential for applications as nonprecious bifunctional catalysts for the OER and ORR in practical devices.